2007
DOI: 10.1213/01.ane.0000253235.39696.fa
|View full text |Cite
|
Sign up to set email alerts
|

The Optimal Motor Response for Infraclavicular Brachial Plexus Block

Abstract: We conclude that having initially located and blocked the musculocutaneous nerve, subsequent injection on a radial response resulted in a slightly more reliable success rate than injection with an ulnar or median response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 8 publications
0
7
0
1
Order By: Relevance
“…In contrast to this, large case series have shown that a radial-type response yields a higher success rate than median-or ulnar-type response. 13,14 However, the conclusions of these studies are not applicable to more proximal VIB and vice versa, mainly because of the fact that a lateral (pericoracoid) approach to infraclavicular blockade implies a difference in cord topography.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to this, large case series have shown that a radial-type response yields a higher success rate than median-or ulnar-type response. 13,14 However, the conclusions of these studies are not applicable to more proximal VIB and vice versa, mainly because of the fact that a lateral (pericoracoid) approach to infraclavicular blockade implies a difference in cord topography.…”
Section: Discussionmentioning
confidence: 99%
“…[28] Secondly, when distal response is obtained, the needle is more centrally placed, resulting in even diffusion of local anaesthetic. [271416] Some authors emphasise that double or multiple stimulation[111718] improves success rate of ICPB, whereas others suggest that stimulation of median nerve,[13] posterior cord[16] or all three cords[11] causes less chances of failure.…”
Section: Discussionmentioning
confidence: 99%
“…This was probably due to more lateral approach in group L and angulated direction of needle in group M. Our results are in agreement with other studies. [5781718]…”
Section: Discussionmentioning
confidence: 99%
“…These investigators registered a 5.8% failure after single injection to the posterior cord compared to 28% following a motor response to the lateral cord. Similarly Minville identified a higher (96%) success rate following a radial motor response compared to 89% and 90% success rates after median or ulnar responses, respectively (Minville et al, 2007). Porter et al published similar findings at the axillary level, arguing that needle placement and injection posterior to the axillary artery may predict successful infraclavicular block (Porter et al, 2005).…”
Section: An Important Anatomical Impingement Pointmentioning
confidence: 92%